Industrialization and the role of trade unions - Dejillas, Leopoldo J. (1991)
The purpose of this article is to present a theory (advanced by some authors) and attempts to clarify, explain, and describe the process and goals of industrialization. the discussion was done primarily with the view of exploring the role that trade unions have played in industrializing societies. The author tried to apply the theory to examine the main efatures of industrialization as it is happening in Asia, particularly in those countries belonging to the Association of Southeast Asian Nations (ASEAN).
Industrialization and world societies -- Industrialization in ASEAN countries -- On the role of trade unions -- Conclusions.
Photocopy.
Includes bibliographical references (p. 48-50)
Keywords: Industrial policy -- Asia, Southeast; Labor unions -- Asia, Southeast; Trade unions -- Asia, Southeast